On the effect of prospective payment system on hospital efficiency and competition for patients in Germany - Helmut Herwartz; Christoph Strumann (Kiel University, Department of Economics, 2011)
The introduction of hospital reimbursement based on diagnosis related groups (DRG) in 2004 has been a conspicuous attempt to increase hospital efficiency in the German health sector. In this paper changes of hospital efficiency, quantified as a Malmquist index decomposition in pure technical efficiency change, are analyzed for periods before and after the reform. We implement a two-stage semi-parametric efficiency model that allows for spatial interdependence among hospitals. The results reveal an enhancement in overall efficiency after the DRG introduction. Moreover, an increase in the magnitude of negative spatial spillovers among German hospital performance can be diagnosed. This result is in line with a rise of competition for (low cost) patients.
Keywords: C21; D61; I11; I18; 330; hospital effciency; data envelopment analysis; spatial analysis; diagnosis related groups